Type 3 inositol 1,4,5-trisphosphate receptor: A calcium channel for all seasons - Mangla, Anjali (Cell Calcium, 2019)
Inositol 1,4,5 trisphosphate receptors (ITPRs) are a family of endoplasmic reticulum Ca(2+) channels essential for the control of intracellular Ca(2+) levels in virtually every mammalian cell type. The three isoforms (ITPR1, ITPR2 and ITPR3) are highly homologous in amino acid sequence, but they differ considerably in terms of biophysical properties, subcellular localization, and tissue distribution. Such differences underscore the variety of cellular responses triggered by each isoform and suggest that the expression/activity of specific isoforms might be linked to particular pathophysiological states. Indeed, recent findings demonstrate that changes in expression of ITPR isoforms are associated with a number of human diseases ranging from fatty liver disease to cancer. ITPR3 is emerging as the isoform that is particularly important in the pathogenesis of various human diseases. Here we review the physiological and pathophysiological roles of ITPR3 in various tissues and the mechanisms by which the expression of this isoform is modulated in health and disease.